IMPACT OF THE INTEGRATED VILLAGE ECONOMIC DEVELOPMENT PROJECT (PROSPEK) OF TRADITIONAL VILLAGES IN DUNGUN, TERENGGANU - Hanapiah, M. T. M.; Zaidi, A. S.; Marzukhi, M. A. (Journal of Engineering and Technology (JET), 2025)
To improve local economies, this study uses the Creativity Index to analyze how an integrated economy affects six (6) traditional villages in Dungun, Terengganu, Malaysia. Working with government agencies to improve rural economies and quality of life was inspired by the Creativity Index. Rural-urban inequities were reduced and natural resources were better used when villagers’ economic interests were harmonized with local values. Agriculture, livestock, aquaculture, SME firms, and rural tourism will be assessed in these communities.